Autoresuscitation: A Case and Discussion of the Lazarus Phenomenon - Kjartan Eskjaer Hannig; Rasmus Wulff Hauritz; Erik Lerkevang Grove (Case Reports in Medicine)
Lazarus phenomenon or autoresuscitation is a very rare condition defined as delayed unassisted return of spontaneous circulation after cessation of cardiopulmonary resuscitation. Based on a case with a 67-year-old male who came back to life after discontinuation of cardiopulmonary resuscitation, we discuss the background and possible countermeasures related to the Lazarus phenomenon.